Measles Vaccination Elicits a Polyfunctional Antibody Response, Which Decays More Rapidly in Early Vaccinated Children. (16th June 2021) - Brinkman, Iris D; Butler, Audrey L; de Wit, Jelle; van Binnendijk, Rob S; Alter, Galit; van Baarle, Debbie
Abstract: Background: Measles outbreaks are reported worldwide and pose a serious threat, especially to young unvaccinated infants. Early measles vaccination given to infants under 12 months of age can induce protective antibody levels, but the long-term antibody functionalities are unknown. Methods: Measles-specific antibody functionality was tested using a systems serology approach for children who received an early measles vaccination at 6–8 or 9–12 months, followed by a regular dose at 14 months of age, and children who only received the vaccination at 14 months. Antibody functionalities comprised complement deposition, cellular cytotoxicity, and neutrophil and cellular phagocytosis. We used Pearson's r correlations between all effector functions to investigate the coordination of the response. Results: Children receiving early measles vaccination at 6–8 or 9–12 months of age show polyfunctional antibody responses. Despite significant lower levels of antibodies in these early-vaccinated children, Fc effector functions were comparable with regular-timed vaccinees at 14 months. However, 3-year follow-up revealed significant decreased polyfunctionality in children who received a first vaccination at 6–8 months of age, but not in children who received the early vaccination at 9–12 months. Conclusions: Antibodies elicited in early-vaccinated children are equally polyfunctional to those elicited from children who received vaccination at 14 months. However, these antibody functionalities decay more rapidly than those induced later in life, which may lead to suboptimal, long-term protection. Abstract : This study shows that regular-timed measles vaccination at 14 months elicits a sustained polyfunctional antibody response. Children receiving an early vaccination at 6–12 month of age showed similar polyfunctionality, but long-term (+3 years) this polyfunctionality decays more rapidly.